EXPLORING GREEN BANDWAGON BEHAVIOR IN ECO-FRIENDLY TUMBLER PURCHASE INTENTION - Rinda Andriana; Akbar Fathoni Husena; Mohamad Iqbal Fawzi (CV. Denasya Smart Publisher, 2026)
This study examines the influence of materialism and social comparison on green purchase intention through the mediating role of green bandwagon behavior in the context of eco-friendly tumbler products. The growing popularity of sustainable lifestyle products has shifted green consumption beyond environmental concerns toward social and symbolic motivations. A quantitative approach was employed using Structural Equation Modelling–Partial Least Squares (SEM-PLS) based on data collected from 130 Indonesian respondents who were familiar with the Ecentio eco-friendly tumbler brand but had never purchased the product. The results show that materialism and social comparison positively influence green bandwagon behavior, while green bandwagon behavior positively influences green purchase intention. However, green bandwagon behavior does not significantly mediate the relationships between materialism, social comparison, and green purchase intention. These findings suggest that social and status-oriented motivations encourage trend-following behavior but are insufficient to generate strong purchase intentions. Practically, eco-friendly brands should combine social trend marketing with clear communication of product quality, health benefits, and environmental value to strengthen purchase intention